PERTUMBUHAN RUMPUT BENGGALA (PANICUM MAXIMUM CV. JACQ) YANG DIBERIKAN PUPUK BIO-SLURRY TERNAK BABI - Kaligis, Johanes; Telleng, M.M.; Soputan, J.E.M.; Kaunang, W.B. (ZOOTEC, 2019)
THE GROWTH OF BENGAL GRASS (Panicum maximum cv. Jacq) GIVEN BIO-SLURRY FERTILIZER OF PIG. The purpose of this study is to determine the effect of bio-slurry fertilizer on the growth of Bengal grass. This study uses organic material fertilizer derived from biogas from pigs for the growth of Bengal grass. A completely randomized design (CRD) with 4 treatments had been used for data analysis. Treatments design as follows: B0: without fertilizer application, B1: 10 tons / ha (25 g / polybag), B2: 20 tons / ha (50g / polybag), B3: 30 tons / ha (75 g /polybag) and was conducted in four replications. The results showed that the treatment of Bio-slurry fertilizer have a very significant effect (P <0.01) on plant height, number of leaves, and number of seedlings. Application of bio-slurry fertilizer for pigs on Bengal grass (Panicum maximum cv. Jacq) up to a dose of 75 grams / polybag in B3 treatment produced the best growth with plant height of 114.44 cm, number of leaves 10.06 strands, and number of 3.00 seedlings..Keywords: growth, bengal grass, bio-slurry.